Tipologi Pemikiran Akidah Netizen pada Konten Dakwah Digital: Analisis Komentar Podcast Escape Episode 21 - Fathi Dafa Nazhari Achmad; Leoma Callista Fawwaz; Rabbiatul Adawiyah (Program Studi Komunikasi dan Penyiaran Islam, STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2026)
The rapid development of digital technology has changed the way religious messages are communicated and discussed in society. Social media, particularly YouTube, has become a platform that not only facilitates the dissemination of Islamic teachings but also encourages users to express their views through interactive discussions in the comment section. One example is Podcast Escape Episode 21 featuring Felix Siauw and Onadio Leonardo, which received various responses reflecting different religious perspectives. This study aims to identify and describe the typology of netizens' religious thought expressed in the podcast's comment section. A descriptive qualitative approach with a post-positivist paradigm was employed. Data were collected through observation, documentation, and qualitative content analysis of selected comments related to issues of radicalism, liberalism, and religious moderation. The findings indicate three dominant typologies of religious thought, namely textual-conservative, rational-liberal, and moderate (wasathiyah-digital). These typologies illustrate that digital platforms have become spaces where different religious understandings are expressed, debated, and negotiated by the public. The study concludes that strengthening digital literacy and promoting religious moderation are important to encourage constructive interaction and reduce the potential for polarization in digital religious discourse.